Contradictions in a distance course for a marginalized population at a Middle Eastern university - Irshat Madyarov (Athabasca University Press, 2012)
This study explores six cases of non-native English speaking students engaged in a distance English-medium course on critical thinking at a university in Iran. Framed within activity theory, the study investigated students’ course-related activity systems with a particular focus on contradictions that underlie any human activity. The construct of contradictions provides a theoretical lens to understand a web of relationships among a number of elements in course-related activities situated in a cultural-historical setting beset with political controversies, technological challenges, and needs for a bilingual curriculum. The findings indicate that all student participants had multiple activity systems within the course environment. Most participants had primary, secondary, and quaternary contradictions that had positive and negative consequences on the expansion of their activity systems. Discussion also includes practical implications for the distance university under study that could potentially be applied to similar distance schools.